2010
DOI: 10.1095/biolreprod.110.083410
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies Affect Human Endometrial Angiogenesis1

Abstract: Antiphospholipid antibodies (aPL) represent an important risk factor for thrombosis and recurrent miscarriage in patients with antiphospholipid syndrome (APS). The mechanisms of aPL-mediated pregnancy failure have been researched. Previous studies demonstrated that aPL bind trophoblast cells, reducing proliferation, human chorionic gonadotrophin release, and in vitro invasiveness. Recent data suggest that aPL are also able to react with human decidual cells, inducing a proinflammatory phenotype. Decidua, a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 36 publications
4
61
1
5
Order By: Relevance
“…These processes are triggered by the interaction of pathogenic aPL with monocytes, endothelial cells (EC), platelets, trophoblast and endometrial cells, as well as plasma components of the coagulation cascade. 16,17,[26][27][28] Therefore, understanding the proposed hypothesis would stand for a growing evidence for the importance of placental apoptosis through TLRs in the pathogenesis of aPL-mediated pregnancy loss. Pathogenic aPL bind to phospholipid binding proteins of which β2GPI is the best characterized.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are triggered by the interaction of pathogenic aPL with monocytes, endothelial cells (EC), platelets, trophoblast and endometrial cells, as well as plasma components of the coagulation cascade. 16,17,[26][27][28] Therefore, understanding the proposed hypothesis would stand for a growing evidence for the importance of placental apoptosis through TLRs in the pathogenesis of aPL-mediated pregnancy loss. Pathogenic aPL bind to phospholipid binding proteins of which β2GPI is the best characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of endometrial angiogenesis by aPL antibodies has been demonstrated in a recent study assessing in vitro human endometrial endothelial cell (HEEC) angiogenesis and in vivo angiogenesis in a murine model. Human polyclonal IgG aPL antibodies were shown to significantly decrease the number and total length of tubule formation, VEGF and MMP production and NF-B DNA binding activity in HEEC and to reduce new vessel formation in inoculated mice [153].…”
Section: Thrombotic and Non-thrombotic Effects Of Apl Antibodies Assomentioning
confidence: 96%
“…Histopathological examination of products of conception in women with pAPS and pregnancy losses between 7 and 10 weeks gestation attributed these losses to abnormal endovascular trophoblast invasion in decidual vessels rather than excessive villous thrombosis. 35 This finding suggests that aPL cause defective placentation, 36 and that thrombophilia is not the sole explanation for complications of pregnancy in patients with APS. Indeed, antib 2 GPI antibodies have been reported to trigger an inflammatory response in trophoblast cells by increasing secretion of IL-8, MCP-1, GRO-a, and IL-1b.…”
Section: Immunopathology Of Apsmentioning
confidence: 99%
“…38 aPL significantly reduce both VEGF and MMPs production, and at the nuclear level, NFjB DNA binding activity. 36 aPL recognize anionic phospholipids and b 2 GPI, which have adhered onto trophoblast cell structures, and significantly reduce bhCG release and Matrigel invasiveness. 39 Therefore, aPL can impair trophoblast cell maturation, mobility, and invasiveness as well.…”
Section: Immunopathology Of Apsmentioning
confidence: 99%
See 1 more Smart Citation